Affect and engagement in healthy and unhealthy weight control behaviors in college women: An ecological momentary assessment study. (January 2021) - Sala, Margarita; Linde, Jennifer A.; Crosby, Ross D.; Pacanowski, Carly R.
Abstract: Purpose: The relationships between momentary affect and weight control behaviors have been extensively studied in samples of individuals with eating disorders, but we do not know that the established relationships translate to healthy college women. The current study examined the relationship between affect and weight control behaviors in healthy college women. Method: Female college students ( N  = 67) completed measures of negative affect, positive affect, healthy weight control behaviors, and unhealthy weight control behaviors across fourteen days using ecological momentary assessment. Results: Average daily negative affect was inversely associated with daily engagement in unhealthy weight control behaviors, but was not associated with healthy weight control behaviors. Average daily positive affect was not associated with daily engagement in healthy or unhealthy weight control behaviors. Conclusion: Negative affect was inversely associated with engagement in unhealthy weight control behaviors in this female undergraduate sample. Future studies should continue to elucidate the differences in the relationships in samples of individuals with ED psychopathology vs. healthy samples. Highlights: Higher negative affect was associated with lower likelihood of engaging in unhealthy weight control behaviors. Negative affect was not correlated with healthy weight control behaviors. Positive affect was not correlated with weight control behaviors.